2007
DOI: 10.1016/j.rapm.2006.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Novice Behavior Associated With Learning Ultrasound-Guided Peripheral Regional Anesthesia

Abstract: Based on the analysis of the committed errors and the identification of quality-compromising behaviors, we are able to recommend important targets for learning in future training and simulation programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
113
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(120 citation statements)
references
References 14 publications
6
113
0
1
Order By: Relevance
“…3 In a clinical study of USG peripheral nerve blockade, Sites and colleagues found long learning curves and a consistent pattern of errors, including unintentional probe movement, awkward needle holding, and most importantly, poor needle tip visualization. 22 We observed a similar pattern of errors early in training, and believe this was also reflected in the baseline and early HMA metrics. The deliberate practice stations were therefore modified to include drills that required precise localization of the tip of the needle (Table 3).…”
Section: Discussionsupporting
confidence: 71%
“…3 In a clinical study of USG peripheral nerve blockade, Sites and colleagues found long learning curves and a consistent pattern of errors, including unintentional probe movement, awkward needle holding, and most importantly, poor needle tip visualization. 22 We observed a similar pattern of errors early in training, and believe this was also reflected in the baseline and early HMA metrics. The deliberate practice stations were therefore modified to include drills that required precise localization of the tip of the needle (Table 3).…”
Section: Discussionsupporting
confidence: 71%
“…Even after correct target identification, available studies have observed that even experienced practitioners (with > 100 ultrasound-guided nerve blocks) persistently failed to maintain the needle tip in view [15]. A recent cadaveric study reported a 50% incidence of unintentional intraneural (sub epineurium) injection during simulated ultrasound-guided interscalene block [8].…”
Section: ó 2011 the Authorsmentioning
confidence: 99%
“…Ultrasound, Kinect, Simulation, Needle, Volumetric Slicing, OpenGL, OpenCV want to incorporate US into their regional anesthesia practice [5]. Traditionally, this skill set is acquired during anesthesia training through performance of these procedures on patients under supervision.…”
Section: Keywordmentioning
confidence: 99%